Performance Evaluation of a 4 × 20-Gbps OFDM-Based FSO Link Incorporating Hybrid W-MDM Techniques - Singh, Mehtab; Chebaane, Saleh; Ben Khalifa, Sana; Grover, Amit; Dewra, Sanjeev; Angurala, Mohit (Frontiers in Physics, 2021)
Free space optics (FSO) has been recognized as a crucial technique to meet the high-bandwidth requirements in future wireless information transmission links. It provides a feasible solution to the last-mile bottleneck problem due to its merits that include high-speed data transportation and secure and low-latency networks. Due to these merits, FSO is a reliable technology for future health-care and biomedical services like the transmission of biomedical sensor signals. But the main limiting factor in the data transmission employing FSO links is adverse atmospheric weather conditions. This research work reports the designing and simulative evaluation of the performance of a high-speed orthogonal frequency division multiplexing–based free space optics link by incorporating wavelength division multiplexing of two independent frequency channels (193.1 THz and 193.2 THz) along with mode division multiplexing of distinct spatial laser Hermite–Gaussian modes (HG01 and HG03). Four independent 20-Gbps quadrature amplitude-modulated data signals are transported simultaneously under different atmospheric weather conditions using the proposed link. Also, the link performance has been investigated for an increasing beam divergence angle.